2021
DOI: 10.3390/ijms22168709
|View full text |Cite
|
Sign up to set email alerts
|

Presence, Mode of Action, and Application of Pathway Specific Transcription Factors in Aspergillus Biosynthetic Gene Clusters

Abstract: Fungal secondary metabolites are renowned toxins as well as valuable sources of antibiotics, cholesterol-lowering drugs, and immunosuppressants; hence, great efforts were levied to understand how these compounds are genetically regulated. The genes encoding for the enzymes required for synthesizing secondary metabolites are arranged in biosynthetic gene clusters (BGCs). Often, BGCs contain a pathway specific transcription factor (PSTF), a valuable tool in shutting down or turning up production of the BGC produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…We then were interested in searching for the downstream regulators participating in aspernidine production. Because the pkf cluster does not contain a transcription factor, we hypothesized that a cis-acting transcription factor could be contained elsewhere in the genome for function ( 47 ). Thus, we analyzed the gene expression levels of 454 transcription factors and 91 epigenetic factors in A. nidulans genome, which are annotated as putative regulators in the Aspergillus Genome Database (www.aspgd.org/) (data files S1 and S2) ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…We then were interested in searching for the downstream regulators participating in aspernidine production. Because the pkf cluster does not contain a transcription factor, we hypothesized that a cis-acting transcription factor could be contained elsewhere in the genome for function ( 47 ). Thus, we analyzed the gene expression levels of 454 transcription factors and 91 epigenetic factors in A. nidulans genome, which are annotated as putative regulators in the Aspergillus Genome Database (www.aspgd.org/) (data files S1 and S2) ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding both backbone enzymes and tailoring enzymes are necessary for all canonical BGCs. Additionally, the BGCs may contain genes encoding transporters that are found to transfer the SM or its precursor, a cluster‐specific transcription factor that positively regulates the other genes within the BGC (Wang et al ., 2021b), and some genes encoding hypothetical or protective functions (Keller, 2018) (Fig. 1B).…”
Section: Overview Of Secondary Metabolite Cluster Organization and Re...mentioning
confidence: 99%
“…(A. fumigatus, A. nidulans, A. niger, A. flavus and A. oryzae) has been functionally annotated, and their SMs have been identified. BGCs of A. nidulans and A. fumigatus in particular have been systematically studied with recent reviews presenting a full picture of their BGCs and transcription factor regulation of these BGCs (Caesar et al, 2020;Wang et al, 2021b). In antiSMASH online programmes, the number of individual PKS, NRPS, DMAT/Terpenes and other backbone genes are shown to vary considerably from an estimated 37 in A. fumigatus to 89 in A. niger (Table 1).…”
Section: Secondary Metabolite In Aspergillusmentioning
confidence: 99%
“…62 Most recently, Wang et al (2021) summarized that in the case that one BGC has two TFs, one of them behaves as the dominating activator responsible for the production of the SMs, while the other plays another role, such as co-activator, negative regulator, or even without a function in some cases found in Aspergillus nidulans and A. fumigatus. 63 Here, no significant transcriptional changes in the hac genes (except hacF itself) detected in the TgOEhacF mutant suggested that HacF played a minor or a different role in the activation of hac BGC. The further evidence that the transcription of hacF and hacG in the Tg au ΔhacA mutant, which lost the ability to biosynthesize HAs, dropped significantly indicated that the transcription of hacF and hacG relied on the presence of HAs.…”
Section: Journal Ofmentioning
confidence: 99%